Et stykke Heimatschutz-arkitektur i Roskilde. Dronning Margrethes Vej 39 - Furdal, Kim (Historisk Årbog for Roskilde Amt, 2021)
Et stykke Heimatschutz-arkitektur i Roskilde. Dronning Margrethes Vej 39